(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Overview of the role of traditional medicine in support cancer treatment in Viet Nam Method: Scoping review. Results: Among the 4,434 articles found in the database, 15 articles met the selection criteria. These primarily consisted of in vitro experiments and animal studies, cross-sectional descriptive studies and clinical intervention studies comparing outcomes before and after treatment. Conclusion: Studies in traditional medicine supporting cancer treatment in Viet Nam over the past 10 years have primarily focused on in vitro experiments and animal studies but the quantity remains limited. Research on traditional herbal formulas and non-pharmacological methods is also scarce.